Grain prices and mortality: A note on la Michodières law - Jean-Michel Chevet; Cormac Ó Gráda (University College Dublin, Department of Economics, 2004)
Research linking food prices and excess mortality has a long history in applied economics and economic history. It goes back to 1766, when Jean-Baptiste de la Michodière was the first to use empirical data to argue for a positive association between wheat prices and mortality. Here La Michodière's time series are subjected to closer statistical scrutiny: the correlation survives, though it is less strong than some later scholars asserted. We also test for the price-mortality link using cross-section data for the 1690s and 1700s.
hdl:10197/435
Keywords: 330; food prices; famine; economic history; history of economic thought; Getreidepreis; Sterblichkeit